2021
DOI: 10.1111/andr.13133
|View full text |Cite
|
Sign up to set email alerts
|

Male genome influences embryonic development as early as pronuclear stage

Abstract: Background Impaired paternal genome expression may cause poor embryonic development after in vitro fertilization (IVF). Objective To evaluate the expression of male infertility on embryo morphokinetics using a time‐lapse incubator and its impact on IVF cycles. Materials and methods This retrospective cohort study followed patients from January 2017 to August 2019. Patients were divided according to the cause of infertility to male factor (study group) and unexplained infertility (control group) and further sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…Our study conflicted with the work of Hu et al, which suggested that the cumulative live birth rate in young women was not affected by the presence of oocyte degeneration (18).The controversial results may be caused by the different approaches of insemination (IVF vs. ICSI) or the heterogeneity of patients. The severity of male infertility might also contribute to embryo development competence (19) and therefore affect the cumulative outcome. The ICSI cohorts are expected to have more severe male infertility factors than IVF cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Our study conflicted with the work of Hu et al, which suggested that the cumulative live birth rate in young women was not affected by the presence of oocyte degeneration (18).The controversial results may be caused by the different approaches of insemination (IVF vs. ICSI) or the heterogeneity of patients. The severity of male infertility might also contribute to embryo development competence (19) and therefore affect the cumulative outcome. The ICSI cohorts are expected to have more severe male infertility factors than IVF cohorts.…”
Section: Discussionmentioning
confidence: 99%